Programa introdutório à fluidodinâmica computacional com a solução numérica do escoamento de Couette - Moreira, Cláudio Tomás Galvão (2020)
This work propose an introductory program to solve a Couette Flow numerically as a didactical methodology so that the students have an insight view of the true nature of an CFD Software: the numerically resolution of the governing equations, with limitations, simplifications and of extreme complexity.